Efektifitas Puerperal Gymnastic dan Kegel Exercises terhadap Involusi Uterus pada Ibu Postpartum Hari 1 - 3 - Kholisotin Kholisotin; Kholifatun Naziro; Zainal Munir; Ahmad Kholid (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2021)
During labor, women experience many reproductive changes, one of which is uterine involution. If the uterine involution is late to return to normal, it will cause subinvolution, puerperal gymnastic techniques and kegel exercises are the easiest techniques to use and are very effective. The purpose of this study was to determine the effectiveness of puerperal gymnastic and kegel exercises on uterine involution in postpartum mothers day 1-3 at BPM Hj. Nengah Mardani Tenggarang Bondowoso. This type of research uses a pre-experimental research methodology using a two-group interpretation-posttest design, with a sample of 30 respondents. The sampling technique in this study used total sampling. Data analysis used paired sample t test and independent t test. The independent t test results showed that there was no significant difference between puerperal gymnastic and kegel exercises in overcoming uterine involution in postpartum mothers with a p value of 0.039 (p value> Î± 0.05). Of the two techniques, Kegel exercises were more effective in reducing involution. uterus with a mean difference of 6.7333> than the mean puerperal gymnastic of 5.8000.